(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
An enhanced slicing algorithm is given as a solution to the problem of inefficiency that arises during the slicing phase of rapid prototyping that is based on STL models. The approach constructs the integral topology of STL models in advance by utilising a hash table. This makes it possible to acquire con- tours directly. The method then decreases the search range in slicing by building the slicing relation matrix, which may significantly reduce the time cost of slicing. The temporal complexity of the method has been shown to be roughly linear, according to the demonstrations. The approach has been shown to be effective and efficient via application examples, and the findings demonstrate that it performs better than other methods that are currently available, particularly when the STL model is either complicated or huge.